Dual task multimodal physical training in Alzheimer's disease: effect on cognitive functions and muscle strength - Bruno Naves Ferreira; Emmanuel Dias de Sousa Lopes; Isadora Ferreira Henriques; Marina de Melo Reis; Amanda Morais de Pádua; Karina de Figueiredo; Fernanda Aparecida Lopes Magno; Flávia Gomes de Melo Coelho (Universidade Federal de Santa Catarina, 2017)
The aim of this study was to evaluate the effects of dual task multimodal physical training (MPT) on the cognitive functions and muscle strength in older adults with Alzheimer's disease. Participants were 19 subjects with AD in the mild and moderate stages, divided into training group (TG) and control group (CG). The TG performed dual task MPT for 12 weeks. Subjects were evaluated at the pre- and post-intervention moments. The Mini Mental State Examination (MMSE), Clock Drawing Test (CDT) and Frontal Assessment Battery (FAB) were used to assess cognition. For muscle strength, the Chair Lift and Sit Test (CLST) and Manual Grasp Force (MGF) were used. The Wilcoxon test was used to analyze pre and post intragroup moments. The TG showed a significant improvement in FAB and CLST (p≤0.05) and a tendency to improve the MMSE score (p≤0.08). The CG showed significant improvement in CLST (p≤0.05). Dual task MPT improves the frontal cognitive functions and lower limb muscle strength of older adults with AD.